Phylogeny and dating of Aframomum (Zingiberaceae) (2010)
A phylogeny of the African genus Aframomum (Zingiberaceae) is presented based on nuclear ribosomal DNA ITS and plastid trnL-trnF DNA sequences. parsimony and Bayesian analyses were performed on both independent and combined data sets, which were obtained by adding new sequences to already published data. Aframomum, whose sister clade is quite likely to be the genus Renealmia, is shown to be monophyletic in the trees from the analyses of the combined data sets and ITS, but the relationships within the genus are not well supported apart from the clades with accessions from the same species (Aframomum limbatum, A. longiligulatum and A. verrucosum). Dating of the crown node of Aframomum using either Non-Prametric Rate Smoothing or a Bayesian approach using BEAST revealed that it diversified during the late Oligocene to Miocene (8.4 +/-0.1-31.4+/-2.9 Mya), which is older than that suggested by previous authors who postulated that the genus may have speciated during the Pleistocene.